High prevalence of depression symptomology among adolescents in Soweto, South Africa associated with being female and cofactors relating to HIV transmission. Issue 3 (2nd July 2016) - Barhafumwa, Bernard; Dietrich, Janan; Closson, Kalysha; Samji, Hasina; Cescon, Angela; Nkala, Busisiwe; Davis, Jack; Hogg, Robert S.; Kaida, Angela; Gray, Glenda; Miller, Cari L.; ,
ABSTRACT: Adolescents in HIV endemic settings are a priority demographic with respect to HIV prevention. Some studies have shown that behaviours associated with HIV transmission, may be mediated by mental health factors such as depression. We undertook this study to explore the prevalence and associations of depression symptomology among adolescents living in the HIV endemic community of Soweto, South Africa through the Botsha Bophelo Adolescent Health Study (BBAHS). We estimated the prevalence of depression using the Centre for Epidemiological Studies of Depression Scale, using a score of ≥24 to indicate 'probable depression'. Among the 789 adolescents (14–19 years) with depression scores, 262 (33%) met the criteria for probable depression (99 [38%] men and 163 [62%] women; p = 0.061). In multivariable logistic regression, factors independently associated with depression included being female (AOR = 2.44, 95% CI: 1.45–4.00), marijuana use (AOR = 2.67, 95% CI: 1.21–5.93), physical violence (AOR = 1.63, 95% CI: 1.01–2.62), pregnancy (AOR = 2.00, 95% CI: 1.03–3.88) and incarceration (AOR = 2.09, 95% CI: 0.99–4.42). These data indicate that a concerning proportion of adolescents in Soweto may be suffering from depression and those screened as potentially depressed, were more likely to be female and have cofactors relating to increased risk for HIV. As part of a comprehensive HIV prevention strategy, we recommend that depression screening for adolescents be integrated into public and school health programs that triage those suffering into treatment programs.